A Critical Review on the Conversion Degree of Resin Monomers by Direct Analyses - Ana Flavia Sanches Borges; Melody Analia Chase; Ana Liesel Guggiari; Maria Jose Gonzalez; Andreia Rodrigues de Souza Ribeiro; Fernanda Miori Pascon; Antonio Ricardo Zanatta (Brazilian Dental Science)
Abstract